Analisis Konsistensi Perencanaan dan Penganggaran Urusan Pendidikan di Kota Solok Tahun 2016-2019 - Sridarnilawati Sridarnilawati; Suhairi Suhairi; Vima Tista Putriana (Universitas Batanghari Jambi, 2021)
The preparation of planning and budgeting documents greatly contributes to the achievement of regional performance. Consistency in planning and budgeting is an indicator in assessing the performance of local governments. The object of this research is educational affairs. Education affairs are given top priority for the local government of Kota Solok. It is intended that the budget for education affairs reaches more than 20% of the total regional expenditure budget. Types of data are secondary data and primary data. Secondary data are RPJMD, RKPD, KUA, PPAS and APBD and LAKIP while primary data is neglecting to interview members of the Regional Government Budget Team (TAPD), BAPPEDA and OPD who are responsible for Educational Affairs. Assessment of the consistency of planning and budgeting uses the Planning and Budgeting Consolidated Matrix (MKPP) and the causes of inconsistency are interviews with informants who understand and know this. The results of this research consistency of planning and budgeting for educational affairs is very good. The causes of inconsistency in planning and budgeting documents are that the proposed Special Allocation Fund (DAK) was not approved by the Central Government, the intervention of the Government and Members of the Council, the existence of regulations from the Central Government. Analysis of the achievement of the performance of education affairs in the City of Solok shows that in general the achievement of the indicators of education affairs has not been achieved because the achievement of indicators according to each year is.